Arts of subjectivity : a new animism for the post -media era - Glazier, Jacob W. (London [England] : Bloomsbury, 2019)
"Diving into post-structuralist French theory, through American feminism, and emerging out of media studies, this book argues for an ethical and aesthetic form of self-fashioning that runs counter to processes subjection and mediatization. This craft of life, as Plato called it, is a space of disjunction and liberation, between subjectivity and other, where something new and different has the potential to emerge and mould to our likeness."--
Foreword -- Preface -- 1. A New Subjectivity -- 2. Iterations -- 3. Metamodeling -- 4. Cosmology -- 5. Linguistics -- 6. Aesthetics -- 7. Subjectivity, Anew
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Art -- Philosophy; Subjectivity in art; Animism in art; Art and technology; Social & political philosophy; Electronic books